(untitled) (Comprehensive Journal of Science, 2026)
The study aimed to identify the role of artificial intelligence in improving mathematics learning in higher education through the following aspects: examining the current state of using artificial intelligence applications and technologies in teaching and learning mathematics in higher education institutions; identifying the impact of employing artificial intelligence on improving the academic achievement of higher education students in mathematics; exploring the role of artificial intelligence in enhancing students’ motivation and attitudes toward learning mathematics; and identifying the most prominent challenges and obstacles facing the use of artificial intelligence technologies in improving mathematics learning in higher education from the perspectives of students and faculty members. The descriptive approach was adopted due to its suitability for the purposes of the study. The study reached the following results: The results indicated that employing artificial intelligence technologies in mathematics education contributes clearly and significantly to improving the academic achievement of higher education students. The findings showed that artificial intelligence enhances students’ motivation and their positive attitudes toward learning mathematics. The study revealed that the use of artificial intelligence in higher education faces a set of challenges and obstacles, most notably the lack of technical expertise among faculty members, weak technological infrastructure, and high costs, which requires the development of strategic plans to overcome these challenges. The results also revealed a strong relationship between integrating artificial intelligence applications in teaching mathematics and improving students’ critical thinking and problem-solving skills, reflecting the ability of these technologies to promote deep learning rather than mere rote learning.